Innovative Approaches to Soil Rejuvenation and Post-Harvest Management in Sugarcane Production in the Philippines - Oñal, Jr., Paulino A.; Yuan, Bro. Jian Meng; Oñal, Paulino Miguel M. (Future Science / FSH-PH Publications, 2025)
Innovations employed in farming are usually done by integrating the existing sugarcane production technologies. The main purpose of innovation is to increase production and to sustain the sugarcane industry. The study aims to validate some of the soil rejuvenation and post-harvest innovations practiced by the farmers that could affect their sugar production. The descriptive method of research is employed in the study. The 320 sugarcane farmers were randomly identify at the seven locations in the Visayas area of the Philippines using the Slovin’s formula. An instrument used was the validated survey questionnaire used by the group of Oñal in their study since 2021. Frequency count, mean, one-way ANOVA, and Pearson Product Moment Correlation were utilized in the data analyses. Key findings showed that the average production of sugarcane farms in the Visayas was between 50-64 tons per hectare (TC/ha) when grouped by location (alpha = 0.05). Correlation analysis show that application of correct quantity of lime and mill waste have a strong relationship with production (ɑlpha = 0.01), while the correct lime placement (ɑlpha = 0.05) and practice of green manuring (ɑlpha = 0.01) have a moderate relationship, respectively. For post-harvest innovations, correlation analysis implied that the delivery of freshly cut cane to the mill is strongly correlated with the production.